2021
DOI: 10.1016/j.apmr.2021.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Societal Participation Across Diagnostic Groups: Secondary Analyses of 8 Studies Using the Utrecht Scale for Evaluation of Rehabilitation-Participation

Abstract: Differences in societal participation across diagnostic groups: Secondary analyses of eight studies using the Utrecht Scale for Evaluation of Rehabilitation-Participation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
2
2
0
Order By: Relevance
“…As a reference, in other patients with non-COVID-19 (ie, stroke, acquired brain injury, progressive neurological diseases, spinal cord injury and acute coronary syndrome), participation levels between 70.6 and 83.5 have been observed. [35][36][37] In all non-COVID patient groups, patients mainly reported restrictions in work/education, housekeeping, physical exercise and performing leisure activities, which is in accordance with restrictions in participation reported in the current study. 36 37 Moreover, these results showed that higher scores of selfexperienced breathlessness or fatigue and more perceived limitations in daily life in the early phase of rehabilitation were associated with a delayed recovery of participation levels over the first year.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As a reference, in other patients with non-COVID-19 (ie, stroke, acquired brain injury, progressive neurological diseases, spinal cord injury and acute coronary syndrome), participation levels between 70.6 and 83.5 have been observed. [35][36][37] In all non-COVID patient groups, patients mainly reported restrictions in work/education, housekeeping, physical exercise and performing leisure activities, which is in accordance with restrictions in participation reported in the current study. 36 37 Moreover, these results showed that higher scores of selfexperienced breathlessness or fatigue and more perceived limitations in daily life in the early phase of rehabilitation were associated with a delayed recovery of participation levels over the first year.…”
Section: Discussionsupporting
confidence: 88%
“…Mean participation levels increased to 86.1 1 year after ICU discharge. As a reference, in other patients with non-COVID-19 (ie, stroke, acquired brain injury, progressive neurological diseases, spinal cord injury and acute coronary syndrome), participation levels between 70.6 and 83.5 have been observed 35–37. In all non-COVID patient groups, patients mainly reported restrictions in work/education, housekeeping, physical exercise and performing leisure activities, which is in accordance with restrictions in participation reported in the current study 36 37…”
Section: Discussionsupporting
confidence: 87%
“…While there are no clinical cut-offs on this scale, data in the present study were comparted to mean scores for stroke and ABI groups in previous literature. Mean scores for these groups show restrictions to be between 78 and 81 and satisfaction between 68 and 72 ( 16 , 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…To enable comparison with the domain scores of the Life-H, items of the USER-Participation were sorted into 3 domains: Productivity, Leisure, and Social within each scale, as described in a recent publication. 26 …”
Section: Methodsmentioning
confidence: 99%